THE SYSTEM FOR POWER EQUIPMENT BREAK-DOWN SIMULATION - Matchenko, Т.І.; Radetskaya, I.V.; Matchenko, P.Т. (Proceedings of National Aviation University (archive), 2005)
This experience makes it possible to propose an automated system for simulating the nuclear and thermal power plants break-downs directly in the course of operation.